2006
DOI: 10.1007/s10532-006-9068-4
|View full text |Cite
|
Sign up to set email alerts
|

Mass production of bacterial communities adapted to the degradation of volatile organic compounds (TEX)

Abstract: This study focuses on the mass cultivation of bacteria adapted to the degradation of a mixture composed of toluene, ethylbenzene, o-, m- and p-xylenes (TEX). For the cultivation process Substrate Pulse Batch (SPB) technique was adapted under well-automated conditions. The key parameters to be monitored were handled by LabVIEW software including, temperature, pH, dissolved oxygen and turbidity. Other parameters, such as biomass, ammonium or residual substrate concentrations needed offline measurements. SPB tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These results showed that P. putida E41 is more effective for ethylbenzene degradation than other bacteria reported in other studies (Bielefeldt and Stensel, 1999;Deeb and Cohen, 1999;Attaway and Schmidt, 2002;Lee et al, 2002;Li et al, 2006;Lapertot et al, 2007;Plaza et al, 2007).…”
Section: (A ) (B) (C)supporting
confidence: 56%
See 1 more Smart Citation
“…These results showed that P. putida E41 is more effective for ethylbenzene degradation than other bacteria reported in other studies (Bielefeldt and Stensel, 1999;Deeb and Cohen, 1999;Attaway and Schmidt, 2002;Lee et al, 2002;Li et al, 2006;Lapertot et al, 2007;Plaza et al, 2007).…”
Section: (A ) (B) (C)supporting
confidence: 56%
“…Their high water solubility, compared to other fuel components, contribute to their mobility, enabling them to migrate in the subsurface and eventually contaminate drinking water supplies (Blume, 1990;Leiwandowski et al, 1997;Chang et al, 2001;Margesin et al, 2003). In spite of governmental intervention in many countries, their emission into the environment is still increasing (Lapertot et al, 2007). The bioremediation of these substances has become an alternative to the traditional physical and chemical methods, which can be costly and produce hazardous products (Singleton, 1994;Abuhamed et al, 2004;Bordel et al, 2007).…”
mentioning
confidence: 99%
“…which were able to degrade a mixture of toluene, ethylbenzene, and xylenes. 14 These metabolites could protect the bacterial cells against the omnipresence of CB and DCB. Indeed, the two molecules as well as their metabolites of degradation are lipophilic and toxic; they are known to be responsible for cellular and wall damages.…”
Section: Parameters Of Controlmentioning
confidence: 99%
“…The same behavior has already been reported. 14,18,19 In the case of chlorinated solvents, the substrate removal can be directly correlated with the chloride released in the cultivation medium during the reaction phase. Note that this should be distinguished from the full mineralization of the substrate.…”
Section: Cb and Dcb Conversion Spb Techniquementioning
confidence: 99%
“…Among all these procedures, bioremediation appears to be an economical, energy-efficient and environmentally sound approach [3], it is also the cleanest one in the case of BTEX because they can be completely mineralized and do not generate secondary effluent problems [4]. In spite of this, the use of biological elimination methods for VOC is limited by the difficulty of achieving substrate absorption in water at the appropriate concentration.…”
Section: Introductionmentioning
confidence: 99%